The Passing on of the Merchant Discount Rate (MDR) to Consumers and Its Implications for MSME Operators - Ditha Maharani; Azka Habibah; Rina Mulyani; Nabila Rahmadani; Hotma Gustian Sitorus; Annisa Putri Ani; Nandang Najmudin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the legal regulation of Merchant Discount Rate within the Quick Response Code Indonesian Standard payment system and analyzes the implications of passing MDR costs on to consumers for Micro, Small, and Medium Enterprise operators in Indonesia. Employing a non empirical normative legal research design, the study relies exclusively on statutory materials, regulatory documents, scholarly literature, and official publications. The analysis combines statutory and conceptual approaches to evaluate the consistency between legal norms governing MDR allocation and practices reported in the literature. The findings indicate that the regulatory framework clearly positions MDR as a merchant obligation and prohibits the transfer of such costs to consumers. Despite this normative clarity, MDR pass through practices continue to occur due to regulatory literacy gaps, economic pressures faced by MSMEs, digital adoption challenges, and limitations in monitoring and enforcement mechanisms. The study further demonstrates that cost transfer practices generate multidimensional consequences, including reduced consumer trust, weakened price transparency, lower digital payment acceptance, and risks to long term MSME competitiveness. The findings support the need for adaptive regulatory strategies, differentiated MDR policies, and strengthened stakeholder coordination to promote sustainable digital payment governance, consumer protection, and inclusive economic development.